Letter (copy) : Foodstuffs for Spain - Tewson, Vincent
029-0079-001 PORT ST/HP.345. HVT/FC/EK/338. Secretary's. 14th December, 1937. Mr. E. Winstanley, Export Department, Co-operative Wholesale Society Limited, 1, Balloon Street, MANCHESTER, 4. Dear Mr. Winstanley, FOODSTUFFS FOR SPAIN. I thank you for your letter of the 13th instant from which I note the exact quantities of the goods you have sent to the s.s. Hartbridge, and also the arrangements you are making in connection with the Bill of Lading. I hope it will be possible for arrangements to be made for the £2,000 worth of sugar to arrive in Spain before Christmas. In regard to the biscuits, I notice that you do not give any quotation for ships biscuits. I think, however, that when you are assured of a boat being available you could proceed on the basis of one ton of biscuits (ships) and one ton of biscuits (sweet). In regard to the cocoa please include one ton as per your quotation. In view of the fact that supplies of milk are already being sent to Spain please do not, at the moment, proceed further with the enquiries which we have made on this matter. With many thanks for your assistance. Yours sincerely, Assistant Secretary. 292/946/29/79